Nothing About Us Without RIGHTS—Meaningful Engagement of Children and Youth: From Research Prioritization to Clinical Trials, Implementation Science, and Policy. (15th August 2018) - Oliveras, Carlo; Cluver, Lucie; Bernays, Sarah; Armstrong, Alice
Abstract : Abstract: This article presents a new agenda for the meaningful engagement of youth in guiding research and policy. It has been codeveloped with youth, adolescents, and children who are living with and affected by HIV. We set out 6 basic requirements (we call them RIGHTS) that hold across clinical trials, observational studies, implementation science, service delivery, and policy development. These requirements are based on a literature review and in-depth consultations with children, adolescents, and youth, which have taken place over a decade in the HIV/AIDS epidemic. Youth engagement must be adequately Resourced with time, training, technical support, and funds. It must be Impactful, with youth informed of how their inputs have been directly used in research, policy, and programming. It must be Genuine, with youth understanding the intentions of the project and choosing to take part. It is essential that we ensure that participation is Harmless, and that it is responsive to the emotional and mental health needs of youth. Processes of participation should be Teen friendly, designed to be enjoyable and relevant to youth priorities. Finally, regarding Skills building, participation should allow for the competencies and skills developed to be recognized in youth education and career experience (without advertising the HIV aspect if this is inappropriate for young people). We propose that these 6 basic requirements be endorsed by all research organizations, and that they become a core component of research in the HIV response.